Numerical Analysis on the Hemodynamic Effects of Asymmetric Stenosis at High Heart Rate in the Left Coronary Artery Bifurcation - Asif Equbal; Paragmoni Kalita (Applications of Modelling and Simulation, 2024)
The branches of the left coronary artery are more critical compared with the right counterpart from the perspective of atherosclerosis and associated heart diseases. Most of the preceding research works studied axisymmetric stenosis shapes in coronary artery bifurcation. However, recent studies indicate that coronary artery blockages are often asymmetric in structures. The present work carries out a novel numerical investigation on the effects of asymmetric degree of stenosis (DOS) having the more typical cosine shape by considering the branches of the left coronary main (LCM) artery, namely, the left circumflex (LCx) and left anterior descending (LAD). The results are analysed to correlate the influence of stenosis in LCx and LAD to the disease severity and progression in terms of hemodynamic parameters including wall shear stress (WSS) profiles, oscillatory shear index (OSI), and pressure drop (PD). The computations reveal that WSS attains lower values over wider regions in the post-stenotic regions in LAD compared with LCx. The values of OSI in the LAD are also higher compared to LCx in all the cases. The peak value of the OSI decreases with the increase in the DOS. However, for higher stenosis degrees, the prominence of OSI is observed even at larger distances in the post-stenosis region. At a given DOS, PD is more in LAD compared with LCx. These effects are found to increase with DOS.